Structure and composition of cocoa agroforests in the humid forest zone of Southern Cameroon - Sonwa, D.J.; Weise, Stephan F.; Nkongmeneck, B.A.; Tchatat, M.; Janssens, M. (Springer, 2017)
The distribution and composition of the tree component inside cocoa agroforests plays an important role in the economic and ecological services offered by these plantations. The presence of these plant components appears to be influenced by several factors controlling the introduction and management of associated plants inside cocoa agroforests. To date, few studies have tried to evaluate the horizontal and vertical distribution of plants inside cocoa plantations in Cameroon. This study determines the structure of cocoa plantations in Southern Cameroon. Field data were collected in 60 cocoa plantations belonging to 12 villages located along a contiguous gradient of market access, population density and resource use intensity in the humid forest zone of southern Cameroon. This study area comprises (i) the sub-region of Yaoundé, (ii) the sub-region of Mbalmayo, and (iii) the sub-region of Ebolowa. Market access, population density and resource use intensity all decreased from the first to the third sub-region. For cocoa and associated plants, we quantified (1) the density (2) the individual number, the species composition and the group uses of plants (edible, timber, medicinal, etc…) distribution across strata, and (3) the basal area in the 60 cocoa plantations located in the three main sub-regions. Results are presented for each sub-region and the whole study area. The paper develops cocoa agroforest typologies and discusses possible implications of cocoa agroforest structure diversity in the achievement of economic and ecological services.